Fostering engineering freshmen’s shifts of attention by using Matlab LiveScript for solving mathematical tasks - Albano, Giovannina; Telloni, Agnese Ilaria (Teaching Mathematics and Computer Science, 2024)
We designed an experimental path including a summative assessment phase, where engineering freshmen are involved in solving mathematical tasks by using Matlab LiveScripts. We analyzed the students’ answers to a questionnaire about their perceived impact of the use of Matlab on their way to solve mathematical tasks. The main result is that students show shifts of attention from computations to other aspects of problem solving, moving from an operational to a structural view of mathematics. Subject Classification: 97U70, 97H60